Electrolyte for high-nickel positive electrode, lithium ion battery and electrolyte injection method of lithium ion battery

By using the step-by-step liquid injection process in high-nickel positive electrode lithium-ion batteries, the problems of degradation of cathode stability and increased battery internal resistance caused by high-nickel positive electrode are solved, and the high cycle stability and dynamic performance of the battery are improved.

CN119650839AActive Publication Date: 2025-03-18BATTEROTECH CO LTD

Patent Information

Application Number
CN202411833150.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

When the prior art increases the energy density of the high nickel positive electrode, it leads to a decrease in cathode stability, negative effects such as electrolyte oxidation, transition metal dissolution, structural reconstruction and particle fracture, thereby reducing the cyclic storage performance of the battery cell and increasing the internal resistance of the battery.

Method used

An electrolyte for high nickel positive electrodes is provided, including lithium salts, solvents and film-forming additives. The component ratio of the electrolyte is accurately controlled through a step-by-step liquid injection process to form a dense CEI structure rich in inorganic substances and a stable SEI film to optimize the physical and chemical properties of the electrolyte.

Benefits of technology

Effectively prevent the dissolution and structural damage of the positive electrode transition metal, improve the cycle stability and safety of the battery, while reducing the internal resistance of the battery, improving the dynamic performance and overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650839A_ABST
    Figure CN119650839A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte for a high-nickel positive electrode, a lithium ion battery and a liquid injection method of the lithium ion battery, and relates to the technical field of battery manufacturing. According to the liquid injection method of the lithium ion battery, a first electrolyte with high-concentration lithium salt and a second electrolyte with relatively low viscosity are respectively injected by adopting a first liquid injection process and a second liquid injection process, so that a compact CEI layer is formed on the surface of a high-nickel positive electrode, and linear carbonic ester with relatively low viscosity is added through secondary injection; according to the lithium-ion battery electrolyte disclosed by the invention, the overall viscosity of the electrolyte is greatly reduced, and the ion mobility of a battery cell in circulation is improved, so that the dynamic performance is improved, and the problem that the internal resistance of the battery is increased due to relatively high viscosity caused by high-concentration lithium salt is effectively relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery manufacturing technology, and in particular to an electrolyte for a high-nickel positive electrode, a lithium-ion battery and a method for injecting the electrolyte. Background Art

[0002] Using high nickel layered oxide (Ni>80%) cathodes is an ideal way to increase the energy density of lithium-ion batteries. However, the pursuit of higher energy density from layered oxides comes at the expense of cathode stability. Volume changes caused by gas production at high charge states and positive electrode interface reactions can negatively affect electrolyte oxidation, transition metal dissolution, structural reconstruction, and increased particle fracture, resulting in poor cycle storage performance of the battery cell.

[0003] In the prior art, the negative effects of high nickel positive electrodes are improved by introducing transition metal complex additives, or high concentration lithium salt electrolytes are used to improve the stability of the battery cells. However, the method of introducing transition metal complex additives will increase the internal resistance of the battery cells, and the method of using high concentration lithium salt electrolytes will reduce the conductivity of the battery cells and increase the internal resistance of the battery cells, thereby affecting the dynamic performance and overall performance of the battery.

[0004] Therefore, there is an urgent need to provide an electrolyte for a high-nickel positive electrode, a lithium-ion battery and an injection method thereof, which can improve the negative effects of the high-nickel positive electrode and improve the cycle storage performance of the battery cell, while also avoiding the problem of increased internal resistance of the battery, thereby improving the battery's kinetic performance and overall performance. Summary of the invention

[0005] The present application provides an electrolyte for a high-nickel positive electrode, a lithium-ion battery and a method for injecting the same, in order to solve the problem of increased internal resistance of the battery while solving the negative effects of the high-nickel positive electrode, so as to improve the kinetic performance and overall performance of the battery.

[0006] In a first aspect, the present application provides an electrolyte for a high-nickel positive electrode, a first electrolyte; the first electrolyte is used in the first liquid injection process of a lithium-ion battery, wherein the first electrolyte includes a lithium salt, a solvent, and a film-forming additive, wherein the lithium salt content is 12%-18% of the total amount of the first electrolyte, the solvent content is 77%-83% of the total amount of the first electrolyte, and the film-forming additive content is 1.2%-4% of the total amount of the first electrolyte.

[0007] Through the above scheme, the first electrolyte is used in the first injection process of the lithium-ion battery. This step-by-step injection process helps to accurately control the proportion of each component in the electrolyte and optimize the physical and chemical properties of the electrolyte to meet the application requirements of lithium-ion batteries with high nickel positive electrode materials under high energy density, high voltage and wide temperature range. Among them, the lithium salt accounts for 12%-18% of the total amount of the first electrolyte, the content of the solvent is 77%-83% of the total amount of the first electrolyte, and the content of the film-forming additive is 1.2%-4% of the total amount of the first electrolyte. These formulas and their contents can generate a dense CEI structure rich in inorganic substances after formation, which can effectively prevent the negative effects of the dissolution and structural damage of the positive transition metal of the battery cell during operation, and at the same time can form a stable SEI (solid electrolyte interface), which can achieve the effect of protecting the high nickel positive electrode material and improve the battery performance.

[0008] In one possible design, the lithium salt is lithium bis(fluorosulfonyl)imide or lithium hexafluorophosphate; the solvent is composed of propylene carbonate, ethylene carbonate and ethyl methyl carbonate; and the film-forming additive is composed of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, vinyl sulfate and lithium difluorooxalatoborate.

[0009] Through the above scheme, lithium bis(fluorosulfonyl)imide (LiFSI) has high thermal stability and electrochemical stability. LiFSI can form a stable SEI film, which is beneficial to improve the cycle performance of the battery. At high concentrations, LiFSI can provide more lithium ions, which helps to improve the rate performance and low temperature performance of the battery. High-concentration LiFSI electrolyte can form a solid electrolyte interface rich in LiF, thereby improving the compatibility of the positive and negative electrode interfaces. Lithium hexafluorophosphate (LiPF6) has good ionic conductivity and chemical stability.

[0010] Propylene carbonate (PC) has a high dielectric constant and a low melting point (-49°C), which enables it to provide good ion migration and low-temperature performance when used as a solvent in the electrolyte. Ethylene carbonate (EC) has a high dielectric constant, which is beneficial to improving the ionic conductivity of the electrolyte. Ethyl methyl carbonate (EMC) has good comprehensive properties, including low viscosity and good electrochemical stability, which helps to improve the charge and discharge efficiency and cycle life of the battery.

[0011] Vinyl carbonate (VC) is an electrochemical reduction additive with a higher reduction potential than the organic solvent in the electrolyte. It can be preferentially electrochemically reduced on the electrode surface to form an SEI film with excellent performance. Fluoroethylene carbonate (FEC) can form a LiF-rich SEI film in the battery, improving the battery's cycle performance and safety. 1,3-Propane sultone (PS) as a film-forming additive can improve the battery's room temperature cycle performance. Diethylene sulfate (DTD) has a significant improvement in high-temperature cycle performance, which is beneficial to improving high-temperature cycle performance. LiDFOB has high solubility and conductivity, and can form a passivation film on the Al foil surface and inhibit electrolyte oxidation.

[0012] In a possible design, the concentration of lithium salt is 2M-6M; in the solvent: the content of propylene carbonate is 2%-5% of the total amount of the first electrolyte, the content of ethylene carbonate is 22%-28% of the total amount of the first electrolyte, and the content of ethyl methyl carbonate is 67%-73% of the total amount of the first electrolyte; in the film-forming additives: the content of vinylene carbonate is 0.2%-0.5% of the total amount of the first electrolyte, the content of fluoroethylene carbonate is 0.5%-1% of the total amount of the first electrolyte, the content of 1,3-propane sultone is 0.8%-1.5% of the total amount of the first electrolyte, the content of vinyl sulfate is 1%-2% of the total amount of the first electrolyte, and the content of lithium difluorooxalatoborate is 0.3%-0.6% of the total amount of the first electrolyte.

[0013] Through the above scheme, the concentration of lithium salt is 2M-6M, and the concentration within this range can provide better electrolyte performance. High concentration of lithium salt can increase the lithium ion content of the electrolyte, thereby improving the rate performance and low temperature performance of the battery. At the same time, high concentration electrolyte helps to form a stable SEI film, improving the cycle stability and safety of the battery.

[0014] The problem of electrolyte decomposition at high temperature can be better alleviated by using a solvent composed of PC, EC and EMC, with a PC content of 2%-5%, EC of 22%-28%, and EMC of 67%-73%. The characteristics of different solvents can be balanced to optimize the overall performance of the electrolyte, including ionic conductivity, low temperature performance and electrochemical stability, thereby improving the performance and safety of lithium-ion batteries.

[0015] The content of VC is 0.2% to 0.5%, the content of FEC is 0.5% to 1%, the content of PS is 0.8% to 1.5%, and the content of DTD is 1% to 2%. This combination of film-forming additives optimizes the formation of SEI film and improves the electrochemical performance of the battery through different mechanisms and effects. VC and FEC form SEI film through electrochemical reduction, PS and DTD improve the stability of SEI film through chemical reaction, and LiDFOB improves the cycle performance and safety of the battery by forming LiF-rich SEI film. The content ratio of these additives is designed according to their role and effect in the battery. By adjusting the mutual ratio, the defects caused by a higher content of one of them can be avoided, thereby ensuring the best performance of the battery under different conditions, especially in lithium-ion batteries with high nickel positive electrode materials. These additives help improve the kinetic performance and overall performance of the battery.

[0016] In a possible design, the first electrolyte further includes a wetting additive, and the content of the wetting additive is 0.3%-1% of the total amount of the first electrolyte.

[0017] Through the above scheme, the wetting additive can reduce the surface tension of the electrolyte, improve the wetting ability and penetration ability of the electrolyte to the electrode, and thus improve the electrochemical performance of the battery. By adding the wetting agent, the battery filling time can be effectively shortened and the cycle performance of the battery can be significantly improved. When the amount of wetting agent added reaches 1%, it will have a negative impact on the cycle performance. Therefore, controlling the content of the wetting additive within the range of 0.3%-1% can ensure the battery performance while avoiding potential problems caused by excessive addition.

[0018] In one possible design, the wetting additive is fluorobenzene.

[0019] Through the above scheme, fluorobenzene as a wetting additive can optimize the contact between the electrolyte and the electrode material and improve the kinetic performance of the battery. It can improve the wettability of the electrolyte to the electrode material, thereby improving the charge and discharge performance and cycle stability of the battery. The introduction of fluorobenzene not only solves the problem of co-embedding of lithium ions and PC into graphite, but also improves the physicochemical properties of the electrolyte, showing excellent compatibility with both graphite and NCM811.

[0020] In a second aspect, the present application provides an electrolyte for a high-nickel positive electrode, including a second electrolyte, the second electrolyte is a linear carbonate solvent, and the second electrolyte is used in a second injection process of a lithium-ion battery.

[0021] Through the above scheme, by providing a second electrolyte for use in the second injection process, the electrolyte inside the battery can be supplemented to restore the original conductivity and electrochemical performance of the battery. The linear carbonate solvent has a low viscosity and good electrochemical stability. It helps to improve the ionic conductivity of the electrolyte and the low-temperature performance of the battery. In particular, the linear carbonate solvent in the second injection process enables the high-nickel positive electrode material to meet the stability and compatibility requirements when working under high voltage. The lithium-ion battery with high-nickel positive electrode material meets the application requirements under high energy density, high voltage and wide temperature range, and further optimizes the electrolyte environment of the battery, improves the battery's kinetic performance and low-temperature performance, thereby improving the overall performance of the battery.

[0022] In one possible design, the linear carbonate solvent is diethyl carbonate or ethyl methyl carbonate.

[0023] Through the above examples, diethyl carbonate (DEC) has lower viscosity and good electrochemical stability as a linear carbonate solvent. DEC with lower viscosity helps to improve the ionic conductivity of the electrolyte and the low temperature performance of the battery. Ethyl methyl carbonate (EMC) is used as a linear carbonate solvent mixed with cyclic carbonate to improve the physicochemical properties of the electrolyte. EMC can provide good electrolyte stability and electrochemical performance, and at the same time help to improve the charge and discharge efficiency and cycle life of the battery.

[0024] In one possible design, when the linear carbonate solvent is diethyl carbonate and ethyl methyl carbonate, the ratio of ethyl methyl carbonate to diethyl carbonate is 1:1.

[0025] Through the above scheme, EMC helps to improve the ionic conductivity of the electrolyte due to its lower viscosity, while DEC helps to improve the high temperature performance of the electrolyte. Since high-nickel positive electrode material batteries have high requirements for the stability and compatibility of the electrolyte when working at high voltage, the ratio of DEC to EMC is 1:1, which can make the high-nickel positive electrode material maintain the overall performance of the electrolyte while also improving the thermal stability of the electrolyte to a certain extent, reducing the occurrence of ester exchange reactions, and optimizing the overall performance of the electrolyte by balancing the characteristics of different solvents, which can improve the overall performance of the battery, including cycle stability, charge and discharge efficiency and safety.

[0026] In a third aspect, the present application provides a method for injecting a lithium-ion battery, the method comprising the following steps: forming a soft-pack battery cell and drying the soft-pack battery cell; performing a first injection process, the first injection process comprising injecting a first electrolyte into the soft-pack battery cell, and sealing, standing, and forming the soft-pack battery cell to form a first battery cell, wherein the first electrolyte is any of the first electrolytes described above; performing a second injection process, the second injection process comprising injecting a second electrolyte into the first battery cell, and performing a second sealing to obtain a lithium-ion battery, wherein the second electrolyte is any of the second electrolytes described above.

[0027] Through the above scheme, the soft-pack battery cell needs to be dried before injection to ensure that there is no moisture inside the battery to prevent the battery performance from being damaged. Considering the characteristics of the high-nickel positive electrode material, the first electrolyte is used to inject the soft-pack battery cell for the first time. The first electrolyte includes lithium salt, solvent and film-forming additive, wherein the lithium salt content is 12%-18%, the solvent content is 77%-83%, and the film-forming additive content is 1.2%-4%. After injection, sealing, standing, formation and aging processes are carried out to form the first battery cell. The second electrolyte is used to inject the first battery cell for the second time. The second electrolyte is a linear carbonate solvent, which is sealed and divided for the second time to finally obtain a lithium-ion battery. The first injection mainly forms a stable SEI film and CEI film to improve the cycle stability and safety of the battery. The second injection further optimizes the electrolyte environment, and the linear carbonate solvent with lower viscosity is injected through the second injection to improve the kinetic performance and low temperature performance of the battery. By precisely controlling the proportion of each component in the electrolyte, the electrochemical stability, cycle life and safety of the battery can be effectively managed.

[0028] In one possible design, the injection coefficient is 3g / Ah-4g / Ah, and the ratio of the first injection to the second injection is 82-88 to 12-18.

[0029] Through the above scheme, the injection coefficient is 3g / Ah-4g / Ah, which means that 3 grams of electrolyte needs to be injected for every ampere-hour (Ah) of battery capacity. The appropriate injection coefficient optimizes the internal resistance, cycle life and safety performance of the battery. The ratio of the first injection to the second injection is 82-88 to 12-18. This ratio means that in the total electrolyte, the electrolyte of the first injection accounts for about 82% to 88% of the total electrolyte volume, while the electrolyte of the second injection accounts for about 12% to 18% of the total electrolyte volume. This step-by-step injection process can more finely control the electrolyte environment inside the battery and optimize battery performance. For example, the first injection may focus more on forming a stable SEI film and CEI film, while the second injection may focus more on replenishing the electrolyte to further improve the high temperature performance and cycle stability of the battery. Through this injection method, the battery performance is optimized in a targeted manner at different stages to improve the overall performance and reliability of the battery.

[0030] In a fourth aspect, the present application provides a lithium-ion battery, including a lithium-ion battery obtained by any of the above-mentioned injection methods.

[0031] The beneficial effects of the lithium-ion battery provided in the fourth aspect and each possible design of the fourth aspect can be referred to the beneficial effects brought about by the third aspect and each possible implementation method of the third aspect, which will not be repeated here.

[0032] The above description is only an overview of the technical solution of the embodiment of the present application. In order to more clearly understand the technical means of the embodiment of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the embodiment of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians, other drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 This is a flow chart of a lithium-ion battery injection method provided in one embodiment of the present application. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used in the specification of the application are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification, claims and drawings of this application are intended to cover non-exclusive inclusions.

[0037] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase "embodiments" in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0038] The term "and / or" in this article is only a description of the association relationship of the associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0039] The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects rather than to describe a specific order, and may explicitly or implicitly include one or more of the features.

[0040] In the description of the present application, unless otherwise specified, "plurality" means more than two (including two), and similarly, "multiple groups" means more than two groups (including two).

[0041] It can be seen that the increase of internal resistance of the battery is not conducive to dynamic performance, which mainly refers to the fact that the increase of internal resistance of the battery will reduce the charging and discharging efficiency and power output capacity of the battery. Specifically, the increase of internal resistance will lead to the following problems.

[0042] The increase in internal resistance will cause more Joule heat to be generated when current passes through the battery, causing the battery temperature to rise. The temperature increase not only affects the performance of the battery, but may also affect the safety and life of the battery.

[0043] The increase in internal resistance will cause the voltage drop of the battery to increase during the discharge process, thereby reducing the actual operating voltage of the battery and affecting the battery's output power and discharge time.

[0044] The increase in internal resistance means that during the charging and discharging process, the resistance encountered by the current when flowing through the inside of the battery increases, which will lead to lower charging and discharging efficiency and reduced available capacity of the battery.

[0045] The kinetic performance of a battery refers to its performance at high-rate charge and discharge. Increased internal resistance will lead to increased polarization of the battery at high-rate charge and discharge, thereby reducing the kinetic performance of the battery.

[0046] The ionic conductivity of the electrolyte determines the internal resistance and rate characteristics of the battery. The conductivity of the electrolyte is inversely proportional to the viscosity of the solvent and is also affected by the concentration of the lithium salt and the size of the anion. A decrease in ionic conductivity means that the mobility of lithium ions in the electrolyte decreases, resulting in an increase in the internal resistance of the battery.

[0047] The decrease in electrolyte ion conductivity will increase the difficulty coefficient of lithium ion desolvation process, resulting in an increase in charge transfer impedance, which is not conducive to the formation of negative electrode graphite SEI film.

[0048] The reduction of electrolyte ion conductivity will affect the battery's charge and discharge efficiency and power output capacity, especially under low temperature conditions, where the electrolyte's viscosity increases and conductivity decreases, which is not conducive to the transmission of lithium ions and further increases the battery's internal resistance.

[0049] Therefore, the reduction of electrolyte ion conductivity will directly lead to an increase in the internal resistance of the battery, thereby affecting the kinetic performance and overall performance of the battery. Therefore, optimizing the ionic conductivity of the electrolyte is one of the keys to improving battery performance. In the related art, the method of introducing transition metal complex additives will increase the internal resistance of the battery cell, and the method of using a high concentration of lithium salt electrolyte will reduce the conductivity of the battery cell and increase the internal resistance of the battery cell, thereby affecting the kinetic performance and overall performance of the battery.

[0050] In view of this, the embodiments of the present application provide an electrolyte for a high-nickel positive electrode, a lithium-ion battery and an injection method thereof. In the injection method, a high-concentration lithium salt electrolyte composed of a first electrolyte and a second electrolyte is injected by using a secondary injection method, which not only forms a dense CEI layer on the surface of the high-nickel positive electrode, but also greatly reduces the overall viscosity of the electrolyte by adding a linear carbonate with lower viscosity through the second injection, thereby improving the ion mobility of the battery cell in the cycle, thereby improving the kinetic performance, thereby effectively alleviating the problem of increased internal resistance of the battery caused by the high viscosity brought about by the high concentration of lithium salt.

[0051] In order to enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below.

[0052] Example 1

[0053] In this embodiment, an electrolyte for a high-nickel positive electrode is provided, namely, a first electrolyte; the first electrolyte is used in the first injection process of a lithium-ion battery, wherein the first electrolyte includes a lithium salt, a solvent, and a film-forming additive, wherein the lithium salt content is 12%-18% of the total amount of the first electrolyte, the solvent content is 77%-83% of the total amount of the first electrolyte, and the film-forming additive content is 1.2%-4% of the total amount of the first electrolyte.

[0054] Through the above scheme, the first electrolyte is used in the first injection process of the lithium-ion battery. This step-by-step injection process helps to accurately control the proportion of each component in the electrolyte and optimize the physical and chemical properties of the electrolyte to meet the application requirements of lithium-ion batteries with high nickel positive electrode materials under high energy density, high voltage and wide temperature range. Among them, the lithium salt accounts for 12%-18% of the total amount of the first electrolyte, the content of the solvent is 77%-83% of the total amount of the first electrolyte, and the content of the film-forming additive is 1.2%-4% of the total amount of the first electrolyte. These formulas and their contents can generate a dense CEI structure rich in inorganic substances after formation, which can effectively prevent the negative effects of the dissolution and structural damage of the positive transition metal of the battery cell during operation, and at the same time can form a stable SEI (solid electrolyte interface), which can achieve the effect of protecting the high nickel positive electrode material and improve the battery performance.

[0055] In this embodiment, the lithium salt is lithium bis(fluorosulfonyl)imide or lithium hexafluorophosphate; the solvent is composed of propylene carbonate, ethylene carbonate and ethyl methyl carbonate; and the film-forming additive is composed of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, vinyl sulfate and lithium difluorooxalatoborate.

[0056] Through the above scheme, lithium bis(fluorosulfonyl)imide (LiFSI) has high thermal stability and electrochemical stability. LiFSI can form a stable SEI film, which is beneficial to improve the cycle performance of the battery. At high concentrations, LiFSI can provide more lithium ions, which helps to improve the rate performance and low temperature performance of the battery. High-concentration LiFSI electrolyte can form a solid electrolyte interface rich in LiF, thereby improving the compatibility of the positive and negative electrode interfaces. Lithium hexafluorophosphate (LiPF6) has good ionic conductivity and chemical stability.

[0057] Propylene carbonate (PC) has a high dielectric constant and a low melting point (-49°C), which enables it to provide good ion migration and low-temperature performance when used as a solvent in the electrolyte. Ethylene carbonate (EC) has a high dielectric constant, which is beneficial to improving the ionic conductivity of the electrolyte. Ethyl methyl carbonate (EMC) has good comprehensive properties, including low viscosity and good electrochemical stability, which helps to improve the charge and discharge efficiency and cycle life of the battery.

[0058] Vinyl carbonate (VC) is an electrochemical reduction additive with a higher reduction potential than the organic solvent in the electrolyte. It can be preferentially electrochemically reduced on the electrode surface to form an SEI film with excellent performance. Fluoroethylene carbonate (FEC) can form a LiF-rich SEI film in the battery, improving the battery's cycle performance and safety. 1,3-Propane sultone (PS) as a film-forming additive can improve the battery's room temperature cycle performance. Diethylene sulfate (DTD) has a significant improvement in high-temperature cycle performance, which is beneficial to improving high-temperature cycle performance. LiDFOB has high solubility and conductivity, and can form a passivation film on the Al foil surface and inhibit electrolyte oxidation.

[0059] In this embodiment, the concentration of the lithium salt is 2M-6M. For example, the concentration of the lithium salt may be 2M, 3.5M, 4M, 5M or 6M.

[0060] In this embodiment, in the solvent: the content of propylene carbonate is 2%-5% of the total amount of the first electrolyte, the content of ethylene carbonate is 22%-28% of the total amount of the first electrolyte, and the content of ethyl methyl carbonate is 67%-73% of the total amount of the first electrolyte; in the film-forming additives: the content of vinylene carbonate is 0.2%-0.5% of the total amount of the first electrolyte, the content of fluoroethylene carbonate is 0.5%-1% of the total amount of the first electrolyte, the content of 1,3-propane sultone is 0.8%-1.5% of the total amount of the first electrolyte, the content of vinyl sulfate is 1%-2% of the total amount of the first electrolyte, and the content of lithium difluorooxalatoborate is 0.3%-0.6% of the total amount of the first electrolyte.

[0061] For example, the content of propylene carbonate can be 2%, 3%, 4% or 5% of the total amount of the first electrolyte. The content of ethylene carbonate can be 23%, 24%, 25%, 27% or 28% of the total amount of the first electrolyte. The content of ethyl methyl carbonate can be 67%, 68%, 69%, 70%, 71%, 72% or 73% of the total amount of the first electrolyte.

[0062] For example, among the film-forming additives: the content of vinylene carbonate can be 0.2%, 0.3%, 0.4% or 0.5% of the total amount of the first electrolyte, the content of fluoroethylene carbonate can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1% of the total amount of the first electrolyte, the content of 1,3-propane sultone can be 0.8%, 0.9%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5% of the total amount of the first electrolyte, the content of vinyl sulfate can be 1%, 1.2%, 1.3%, 1.5% or 2% of the total amount of the first electrolyte, and the content of lithium difluorooxalatoborate can be 0.3%, 0.4%, 0.5% or 0.6% of the total amount of the first electrolyte.

[0063] Through the above scheme, the concentration of lithium salt is 2M-6M, and the concentration within this range can provide better electrolyte performance. High concentration of lithium salt can increase the lithium ion content of the electrolyte, thereby improving the rate performance and low temperature performance of the battery. At the same time, high concentration electrolyte helps to form a stable SEI film, improving the cycle stability and safety of the battery.

[0064] The problem of electrolyte decomposition at high temperature can be better alleviated by using a solvent composed of PC, EC and EMC, with a PC content of 2%-5%, EC of 22%-28%, and EMC of 67%-73%. The characteristics of different solvents can be balanced to optimize the overall performance of the electrolyte, including ionic conductivity, low temperature performance and electrochemical stability, thereby improving the performance and safety of lithium-ion batteries.

[0065] For example, the PC content may be 2%, 3%, 4% or 5%.

[0066] For example, the EC may be 22%, 23%, 25%, 26%, or 28%.

[0067] For example, the EMC may be 67%, 68%, 69%, 70% or 71%, 73%.

[0068] The VC content is 0.2% to 0.5%, the FEC content is 0.5% to 1%, the PS content is 0.8% to 1.5%, and the DTD content is 1% to 2%. This combination of film-forming additives optimizes the formation of the SEI film through different mechanisms and effects, and improves the electrochemical performance of the battery. VC and FEC form the SEI film through electrochemical reduction, PS and DTD improve the stability of the SEI film through chemical reactions, and LiDFOB improves the cycle performance and safety of the battery by forming a LiF-rich SEI film.

[0069] For example, the VC content may be 0.2%, 0.3%, 0.4% or 0.5%.

[0070] For example, the PS content may be 0.8%, 0.9%, 1.0%, 1.2%, 1.4% or 1.5%.

[0071] For example, the DTD content may be 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%.

[0072] The content ratio of these additives is designed according to their functions and effects in the battery. By adjusting the mutual ratio, the defects caused by a higher content of one of them can be avoided, thereby ensuring the best performance of the battery under different conditions. Especially in lithium-ion batteries with high nickel positive electrode materials, these additives help to improve the battery's kinetics and overall performance.

[0073] In this embodiment, the first electrolyte further includes a wetting additive, and the content of the wetting additive is 0.3%-1% of the total amount of the first electrolyte.

[0074] For example, the content of the wetting additive may be 0.3%, 0.5%, 0.7%, 0.8% or 1% of the total amount of the first electrolyte.

[0075] Through the above scheme, the wetting additive can reduce the surface tension of the electrolyte, improve the wetting ability and penetration ability of the electrolyte to the electrode, and thus improve the electrochemical performance of the battery. By adding the wetting agent, the battery filling time can be effectively shortened and the cycle performance of the battery can be significantly improved. When the amount of wetting agent added reaches 1%, it will have a negative impact on the cycle performance. Therefore, controlling the content of the wetting additive within the range of 0.3%-1% can ensure the battery performance while avoiding potential problems caused by excessive addition.

[0076] Based on the above embodiments, in this embodiment, an electrolyte for a high-nickel positive electrode is also provided, including a second electrolyte, the second electrolyte is a linear carbonate solvent, and the second electrolyte is used in a second injection process of a lithium-ion battery.

[0077] Through the above scheme, by providing a second electrolyte for use in the second injection process, the electrolyte inside the battery can be supplemented to restore the original conductivity and electrochemical performance of the battery. The linear carbonate solvent has a low viscosity and good electrochemical stability. It helps to improve the ionic conductivity of the electrolyte and the low-temperature performance of the battery. In particular, the linear carbonate solvent in the second injection process enables the high-nickel positive electrode material to meet the stability and compatibility requirements when working under high voltage. The lithium-ion battery with high-nickel positive electrode material meets the application requirements under high energy density, high voltage and wide temperature range, and further optimizes the electrolyte environment of the battery, improves the battery's kinetic performance and low-temperature performance, thereby improving the overall performance of the battery.

[0078] In this embodiment, the linear carbonate solvent is diethyl carbonate or ethyl methyl carbonate.

[0079] Through the above examples, diethyl carbonate (DEC) has lower viscosity and good electrochemical stability as a linear carbonate solvent. DEC with lower viscosity helps to improve the ionic conductivity of the electrolyte and the low temperature performance of the battery. Ethyl methyl carbonate (EMC) is used as a linear carbonate solvent mixed with cyclic carbonate to improve the physicochemical properties of the electrolyte. EMC can provide good electrolyte stability and electrochemical performance, and at the same time help to improve the charge and discharge efficiency and cycle life of the battery.

[0080] Based on the first electrolyte and the second electrolyte provided in the above embodiment, in this embodiment, a method for injecting electrolyte into a lithium ion battery is also provided, the method comprising:

[0081] Step 1: forming a soft-pack battery cell and drying the soft-pack battery cell.

[0082] The steps of forming a soft-pack battery cell include:

[0083] Firstly, NCM811 (nickel, cobalt and manganese are composed in a ratio of 8:1:1) is used as the main material of the positive electrode, mixed with a conductive agent and a binder respectively, and homogenized with NMP to obtain a positive electrode slurry. The positive electrode slurry is coated on aluminum foil and dried, rolled, slid and die-cut to obtain a positive electrode sheet.

[0084] Then, graphite is used as the main material of the negative electrode, mixed with a conductive agent, a binder, and a dispersant respectively, and slurried with deionized water to obtain a negative electrode slurry. The negative electrode slurry is coated on a carbon-coated copper foil and subjected to drying, rolling, slitting, and die-cutting processes to obtain a negative electrode sheet.

[0085] Finally, the microporous polypropylene film is used as a separator, and the positive electrode sheet, the negative electrode sheet and the separator are made into a lithium-ion battery through the process of stacking-hot pressing-baking-liquid injection-high temperature standing-formation-aging-capacity separation-OCV.

[0086] Step 2, performing a first liquid injection process, the first liquid injection process includes injecting a first electrolyte into the soft-pack battery cell, and sealing, standing, and forming the soft-pack battery cell to form a first battery cell; wherein the first electrolyte is any of the first electrolytes mentioned above.

[0087] Step 3, performing a second liquid injection process, the second liquid injection process includes injecting a second electrolyte into the first battery cell and performing a second sealing to obtain a lithium-ion battery, wherein the second electrolyte is any of the second electrolytes mentioned above.

[0088] Through the above scheme, the soft-pack battery cell needs to be dried before injection to ensure that there is no moisture inside the battery to prevent damage to the battery performance. Taking into account the characteristics of the high-nickel positive electrode material, the first electrolyte is used to perform the first injection process on the soft-pack battery cell. The first injection mainly forms a stable SEI film and CEI film to improve the cycle stability and safety of the battery. Using the second electrolyte to perform the second injection process on the first battery cell can further optimize the battery electrolyte environment, and inject a linear carbonate solvent with lower viscosity through the second injection to improve the battery's kinetic performance and low-temperature performance. By precisely controlling the proportion of each component in the electrolyte, the electrochemical stability, cycle life and safety of the battery can be effectively managed.

[0089] In one possible design, the injection coefficient is 3g / Ah-4g / Ah, and the ratio of the first injection to the second injection is 82-88 to 12-18.

[0090] Through the above scheme, the injection coefficient is 3g / Ah-4g / Ah, which means that 3 grams to 4 grams of electrolyte need to be injected for every ampere-hour (Ah) of battery capacity. The appropriate injection coefficient optimizes the internal resistance, cycle life and safety performance of the battery. The ratio of the first injection to the second injection is 82-88 to 12-18. This ratio means that in the total electrolyte, the electrolyte of the first injection accounts for about 82% to 88% of the total electrolyte, and the electrolyte of the second injection accounts for about 12% to 18% of the total electrolyte.

[0091] For example, the electrolyte of the first injection can be 82%, 83%, 84%, 85%, 86%, 87% or 88% of the total electrolyte volume, and the electrolyte of the second injection can be approximately 12%, 13%, 14%, 15%, 16% or 18% of the total electrolyte volume.

[0092] This step-by-step injection process can more finely control the electrolyte environment inside the battery and optimize battery performance. For example, the first injection may focus more on forming a stable SEI film and CEI film, while the second injection may focus more on replenishing the electrolyte to further improve the high-temperature performance and cycle stability of the battery. Through this injection method, the battery performance is optimized in a targeted manner at different stages to improve the overall performance and reliability of the battery.

[0093] Based on the above embodiments, the present application further provides a lithium-ion battery, including a lithium-ion battery obtained by any of the above injection methods. Since the injection method and effects of the lithium-ion battery have been described in detail in the previous embodiments, the present application will not repeat them here.

[0094] Example 2

[0095] Based on the above embodiments, a lithium ion battery is provided in this embodiment, which is obtained by the following injection method:

[0096] A 5Ah soft-pack battery cell was made, and the electrolyte was injected according to the total amount of injection obtained at a ratio of 3g / Ah;

[0097] Performing a first liquid injection process, the first liquid injection process includes injecting a first electrolyte into the soft-pack battery cell to obtain a first battery cell;

[0098] A second liquid injection process is performed, which includes injecting a second electrolyte into the first battery cell and performing a second sealing to obtain a lithium-ion battery.

[0099] In this embodiment, the ratio of the first electrolyte in the first liquid injection process to the second electrolyte in the second liquid injection process is 85:15.

[0100] In this embodiment, the electrolyte for the high-nickel positive electrode includes a first electrolyte, and the first electrolyte includes a lithium salt, a solvent, a film-forming additive, and a wetting additive.

[0101] Among them, the lithium salt is 3MLiFSi, the solvent is PC:EC:EMC=5:25:70, the film-forming additives are 0.3% VC, 0.6% FEC, 1% PS, 1.5% DTD, 0.6% LiODFB, and the wetting additive is 0.5% fluorobenzene FB.

[0102] In this embodiment, the electrolyte for the high-nickel positive electrode also includes a second electrolyte, the second electrolyte includes DEC and EMC, and the ratio of DEC to EMC is 1:1.

[0103] The obtained lithium-ion battery was subjected to electrochemical testing, and the test results are shown in Table 1.

[0104] Example 3

[0105] In the lithium-ion battery provided in this embodiment, in the injection method, the lithium salt of the first electrolyte in the first injection process is 2M LiFSi. That is, the difference between this embodiment and embodiment 2 is that the lithium salt of the first electrolyte in the first injection process in embodiment 2 is 3MLiFSi, while the lithium salt of the first electrolyte in the first injection process in embodiment 3 is 2M LiFSi, and the rest is the same as embodiment 1.

[0106] The obtained lithium-ion battery was subjected to electrochemical testing, and the test results are shown in Table 1.

[0107] Example 4

[0108] In the lithium-ion battery provided in this embodiment, in the injection method, the lithium salt of the first electrolyte in the first injection process is 5M LiFSi. That is, the difference between this embodiment and embodiment 2 is that the lithium salt of the first electrolyte in the first injection process in embodiment 2 is 3MLiFSi, while the lithium salt of the first electrolyte in the first injection process in embodiment 4 is 5M LiFSi, and the rest is the same as embodiment 2.

[0109] The obtained lithium-ion battery was subjected to electrochemical testing, and the test results are shown in Table 1.

[0110] Example 5

[0111] In the lithium-ion battery provided in this embodiment, in the injection method, the lithium salt of the first electrolyte in the first injection process is 3M LiPF6. That is, the difference between this embodiment and embodiment 2 is that the lithium salt of the first electrolyte in the first injection process in embodiment 2 is 3MLiFSi, while the lithium salt of the first electrolyte in embodiment 5 is 3M LiPF6, and the rest is the same as embodiment 2.

[0112] The obtained lithium-ion battery was subjected to electrochemical testing, and the test results are shown in Table 1.

[0113] Example 6

[0114] In the lithium-ion battery provided in this embodiment, in the injection method, the lithium salt of the first electrolyte in the first injection process is 1.5M LiPF6 and 1.5M LiFSi. That is, the difference between Example 6 and Example 2 is that the lithium salt of the first electrolyte in the first injection process in Example 2 is 3MLiFSi, while the lithium salt of the first electrolyte in Example 6 is 1.5M LiPF6 and 1.5M LiFSi, and the rest is the same as Example 2.

[0115] The obtained lithium-ion battery was subjected to electrochemical testing, and the test results are shown in Table 1.

[0116] Example 7

[0117] In the lithium-ion battery provided in this embodiment, in the injection method, the solvent of the first electrolyte in the first injection process is EC:EMC=30:70. That is, the difference between Example 7 and Example 2 is that the solvent of the first electrolyte in the first injection process in Example 2 is PC:EC:EMC=5:25:70, while the solvent of the first electrolyte in Example 7 is EC:EMC=30:70, and the rest is the same as Example 2.

[0118] The obtained lithium-ion battery was subjected to electrochemical testing, and the test results are shown in Table 1.

[0119] Example 8

[0120] In the lithium-ion battery provided in this embodiment, in the injection method, the first electrolyte in the first injection process does not include a wetting additive. That is, the difference between Example 8 and Example 2 is that 0.5% FB is used as a wetting additive in the first injection process in Example 2, while the first electrolyte in Example 8 does not include a wetting additive, and the rest is the same as Example 2.

[0121] The obtained lithium-ion battery was subjected to electrochemical testing, and the test results are shown in Table 1.

[0122] Comparative Example 1

[0123] The lithium ion battery provided in Comparative Example 1 has the same lithium salt concentration, solvent ratio, additive type and content as those in Example 2 in its injection method, except that the lithium ion battery is obtained by only the first injection process in the comparative example. The injection method of Comparative Example 1 is as follows:

[0124] A method for injecting liquid into a lithium-ion battery is provided, comprising:

[0125] A 5Ah soft-pack battery cell was made, and the electrolyte was injected according to the total amount of injection obtained at a ratio of 3g / Ah;

[0126] The first liquid injection process is performed, and the first liquid injection process includes injecting the first electrolyte and the second electrolyte into the soft-pack battery cell to obtain a lithium-ion battery.

[0127] The obtained lithium-ion battery was subjected to electrochemical testing, and the test results are shown in Table 1.

[0128] Performance Test:

[0129] mAh / g: refers to the ratio of the capacity of the active material inside the battery to its mass, usually used to measure the performance of battery materials. In lithium-ion batteries, this usually involves the gram capacity of the positive and negative electrode materials, that is, how much electricity can be released or stored per gram of material (mAh / g).

[0130] During this test, the battery cell is charged and discharged at a rate of 0.33C before testing, and the gram capacity of the battery cell is calculated based on the discharge capacity and the mass of the active material.

[0131] 45℃ cycle 500-cycle capacity retention rate (1C / 1C): refers to the capacity retention rate after 500 cycles of charging and discharging the battery cell at 45℃ at a rate of 1C.

[0132] 60℃ storage retention rate (60D): The fully charged battery cell is placed in a constant temperature box at 60℃ for 60 days, and then discharged to calculate the ratio to the initial capacity.

[0133] 55℃ storage volume expansion (60D): The fully charged battery cell is placed in a 55℃ constant temperature box for 60 days. The volume expansion rate of the battery cell after storage is calculated by the water displacement method to evaluate the gas production performance of the battery.

[0134] The lithium ion batteries obtained in the above-mentioned Examples 2, 3, 4, 5, 6, 7, 8 and Comparative Example 1 were tested for the above-mentioned performance indicators, and the results are shown in Table 1.

[0135] Table 1:

[0136]

[0137] It can be seen from Table 1 that:

[0138] The comparison of the results of Examples 2 to 8 with the results of Comparative Example 1 shows that the lithium-ion battery obtained by the injection method provided by the present application is superior to the conventional lithium-ion battery in terms of standard juncture capacity, 500-cycle capacity retention rate, storage retention rate, and storage volume expansion performance. The secondary injection method effectively improves the cycle and storage performance of the battery cell and suppresses gas production.

[0139] The comparison results of Example 2, Example 3 and Example 4 show that the effect of selecting 3MLiFSi as lithium salt is better than 2MLiFSi and 5MLiFSi. This is because excessive or insufficient concentration of lithium salt will affect the lithium ion content of the electrolyte, thereby affecting the cycle stability and safety of the battery.

[0140] The comparison results of Example 2 and Examples 5 and 6 show that the effect of selecting MLiFSi as the lithium salt may be better than LiPF6 or the combination of MLiFSi and LiPF6.

[0141] The comparison results of Example 2 and Example 7 show that partial replacement of EC with PC can alleviate the decomposition of the electrolyte at high temperature, wherein the PC content in the solvent is ≤5%, which can improve the cycle stability, storage retention rate and gas generation suppression of the battery.

[0142] The comparison results of Example 2 and Example 8 show that the introduction of fluorobenzene not only improves the wetting of the electrolyte to the electrode, but also alleviates the co-embedding problem of Li+-PC in graphite, which can improve the battery's cycle stability, storage retention rate and gas production inhibition.

[0143] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. An electrolyte for a high nickel positive electrode, characterized in that: include: a first electrolyte; The first electrolyte is used in the first injection process of a lithium-ion battery, wherein the first electrolyte includes a lithium salt, a solvent, and a film-forming additive, wherein the lithium salt content is 12%-18% of the total amount of the first electrolyte, the solvent content is 77%-83% of the total amount of the first electrolyte, and the film-forming additive content is 1.2%-4% of the total amount of the first electrolyte.

2. The electrolyte according to claim 1, characterized in that The lithium salt is lithium bis(fluorosulfonyl)imide or lithium hexafluorophosphate; The solvent consists of propylene carbonate, ethylene carbonate and ethyl methyl carbonate; The film-forming additive consists of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, vinyl sulfate and lithium difluorooxalatoborate.

3. The electrolyte according to claim 2, characterized in that The concentration of the lithium salt is 2M-6M; In the solvent: the content of propylene carbonate is 2%-5% of the total amount of the first electrolyte, the content of ethylene carbonate is 22%-28% of the total amount of the first electrolyte, and the content of ethyl methyl carbonate is 67%-73% of the total amount of the first electrolyte; Among the film-forming additives: the content of vinylene carbonate is 0.2% to 0.5% of the total amount of the first electrolyte, the content of fluoroethylene carbonate is 0.5% to 1% of the total amount of the first electrolyte, the content of 1,3-propane sultone is 0.8% to 1.5% of the total amount of the first electrolyte, the content of vinyl sulfate is 1% to 2% of the total amount of the first electrolyte, and the content of lithium difluorooxalatoborate is 0.3% to 0.6% of the total amount of the first electrolyte.

4. The electrolyte according to claim 1, characterized in that The first electrolyte also includes a wetting additive, and the content of the wetting additive is 0.3%-1% of the total amount of the first electrolyte.

5. The electrolyte according to claim 4, characterized in that The wetting additive is fluorobenzene.

6. An electrolyte for a high nickel positive electrode, characterized in that: include: a second electrolyte; The second electrolyte is a linear carbonate solvent, and the second electrolyte is used in the second electrolyte injection process of the lithium-ion battery.

7. The electrolyte according to claim 6, characterized in that The linear carbonate solvent is diethyl carbonate or ethyl methyl carbonate.

8. The electrolyte according to claim 7, characterized in that When the linear carbonate solvent is diethyl carbonate and ethyl methyl carbonate, the ratio of diethyl carbonate to ethyl methyl carbonate is 1:

1.

9. A method for injecting liquid into a lithium ion battery, characterized in that: The method comprises the steps of: Forming a soft-pack battery core, and drying the soft-pack battery core; Performing a first liquid injection process, the first liquid injection process comprising injecting a first electrolyte into the soft-pack battery cell, and performing sealing, standing, and forming to form a first battery cell, wherein the first electrolyte is the first electrolyte according to any one of claims 1 to 5; A second liquid injection process is performed, wherein the second liquid injection process includes injecting a second electrolyte into the first battery cell and performing a secondary sealing to obtain a lithium-ion battery, wherein the second electrolyte is the second electrolyte described in any one of claims 6-8.

10. The liquid injection method according to claim 9, characterized in that: The injection coefficient is 3g / Ah-4g / Ah, and the ratio of the total amount of the first electrolyte in the first injection process to the total amount of the second electrolyte in the second injection process is 82-88 to 12-18.

11. A lithium ion battery, characterized in that: A lithium ion battery obtained by the liquid injection method according to claim 9 or 10.

Citation Information

Patent Citations

  • Electrolyte taking propylene carbonate as main solvent and secondarily liquid injected lithium ion battery

    CN105449281A

  • Lithium ion battery electrolyte, electrolyte injection method and lithium ion battery

    CN114583260A

  • Electrolyte injection method and application thereof

    CN116231083A

  • Method for preparing lithium ion secondary battery and lithium ion secondary battery prepared thereby

    CN116936925A

  • Secondary liquid injection method and application thereof

    WO2023050767A1

Cited By

  • Electrolyte for high-nickel positive electrode, lithium-ion battery, and liquid injection method therefor

    WO2026123663A1